1981
DOI: 10.1172/jci110311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Lipotropin and β-Lipotropin-derived Peptides on Aldosterone Production in the Rat Adrenal Gland

Abstract: A B S T R A C T To investigate the role of non-ACTH pituitary peptides on steroidogenesis, we studied the effects of synthetic 3-lipotropin, (8-melanotropin, and p-endorphin on aldosterone and corticosterone stimulation using rat adrenal collagenase-dispersed capsular and decapsular cells. f8-lipotropin induced a significant aldosterone stimulation in a dose-dependent fashion (10 nM-1 ,uM). 8-endorphin, which is the carboxyterminal fragment of 8-lipotropin, did not stimulate aldosterone production at the doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…In contrast, Kern et al (20) found no effect on plasma aldosterone or plasma cortisol with bolus administrations of up to 15 mg ß-endorphin in four normal human subjects. Our own in vitro results with ß-endorphin speak against a direct effect of this peptide on the adrenal cortex, thereby confirming the findings ofMatsuoka et al (3) in rat adrenal cell preparations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, Kern et al (20) found no effect on plasma aldosterone or plasma cortisol with bolus administrations of up to 15 mg ß-endorphin in four normal human subjects. Our own in vitro results with ß-endorphin speak against a direct effect of this peptide on the adrenal cortex, thereby confirming the findings ofMatsuoka et al (3) in rat adrenal cell preparations.…”
Section: Discussionsupporting
confidence: 91%
“…seribed a stimulatory effect of synthetic ß-endorphin Stimülatoiy effects of proopiomelanocortin-derived on aldosterone secretion which could not be conpeptides on isolated rat adrenal cells have recently firmed by Matsuoka et al (3). Synthetic Lys-y 3 -mebeen reported:…”
mentioning
confidence: 99%
“…These include: f3-endorphin (7), f3-lipotropin (8), a-MSH (9, 10), -y-MSH (I 1, 12), and aldosterone-stimulating factor (13,14). Aldosterone-stimulating factor and y-MSH have both been reported to be elevated in patients with idiopathic aldosteronism (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…However, a relatively high peptide dose (10 sg/100 g body wt) was needed to increase aldosterone secretion. Recently, it has been reported that ,LPH and fMSH selectively stimulated aldosterone production in collagenase-dispersed capsular cells from rat adrenal glands (20,21). The C-terminal #lLPH fragments, ,BEND and Met-enkephalin, had no effect on steroidogenesis in this in vitro system.…”
Section: Resultsmentioning
confidence: 71%
“…Furthermore, the amino-terminal region of pro-OLMC has been reported to potentiate slightly but significantly the action of (1-24) ACTH in isolated rat adrenocortical cells (16). In this study synthetic aMSH, synthetic porcine flMSH, synthetic human fEND and highly purified ovine flLPH were found to have no Recently, I3LPH and #lMSH were observed to stimulate aldosterone production in collagenase-dispersed rat capsular adrenal cells (zona glomerulosa cells) without affecting corticosterone production in zona fasciculata and reticularis cells (20,21). Beta-endorphin and Met-or leucine(Leu)-enkephalin had no effect on steroid production by adrenal cells in this system.…”
mentioning
confidence: 64%